Nonisothermal Thermogravimetric Analysis of Thai Lignite with High CaO Content - Pakamon Pintana; Nakorn Tippayawong (The Scientific World Journal)
Thermal behaviors and combustion kinetics of Thai lignite with different SO3-free CaO contents were investigated. Nonisothermal thermogravimetric method was carried out under oxygen environment at heating rates of 10, 30, and 50°C min−1 from ambient up to 1300°C. Flynn-Wall-Ozawa (FWO) and Kissinger-Akahira-Sunose (KAS) methods were adopted to estimate the apparent activation energy (E) for the thermal decomposition of these coals. Different thermal degradation behaviors were observed in lignites with low (14%) and high (42%) CaO content. Activation energy of the lignite combustion was found to vary with the conversion fraction. In comparison with the KAS method, higher E values were obtained by the FWO method for all conversions considered. High CaO lignite was observed to have higher activation energy than the low CaO coal.